Intelligent Science and Intelligent Data Engineering Second Sino-foreign-interchange Workshop, IScIDE 2011, Xi$1 (Ban, China, October 23-25, 2011, Revised Selected Papers /s - Zhang, Yanning; Zhou, Zhi-Hua.; Zhang, Changshui; Li, Ying.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the proceedings of the Sino-foreign-interchange Workshop on Intelligence Science and Intelligent Data Engineering, IScIDE 2011, held in Xi'an, China, in October 2011. The 97 papers presented were carefully peer-reviewed and selected from 389 submissions. The IScIDE papers in this volume are organized in topical sections on machine learning and computational intelligence; pattern recognition; computer vision and image processing; graphics and computer visualization; knowledge discovering, data mining, web mining; multimedia processing and application.
machine learning and computational intelligence -- pattern recognition -- computer vision and image processing -- graphics and computer visualization -- knowledge discovering, data mining, web mining -- multimedia processing and application.
Keywords: Computer science; Data mining; Multimedia systems; Artificial intelligence; Computer graphics; Computer vision; Optical pattern recognition; Computer Science; Image Processing and Computer Vision; Pattern Recognition; Computer Graphics; Artificial Intelligence (incl. Robotics).; Multimedia Information Systems; Data Mining and Knowledge Discovery